ECONOMIA EXTRATIVA DA FIBRA DE BURITI (MAURITIA FLEXUOSA) PARA O DESENVOLVIMENTO SUSTENTÁVEL DA MICRORREGIÃO DOS LENÇÓIS MARANHENSES, MA NA ATUALIDADE - Sousa, Késsia Rosaria de (2015)
The present dissertation presents the relationship between extractive economic practice of buriti fiber crafts and sustainable development in the micro region of Lençóis, taking as temporal focus, today. To that end, discussions were raised on the subject, sustainable development, it was traced Brazilian extractive panorama, state and local, showing the economic potential of Non Timber Forest Products and its viability over the sustainability of natural resources and improving the quality of life of the population dependent on this practice as complementary and main source of income. The data rescue in the last decade allowed to point the panorama of micro, its evolutions and regressions as the indices of development and population conditions of life. The information about the extractive practices were drawn from current studies initiated in 2009 and findados in 2012 from bodies such as the Institute of Applied Economic Research (IPEA), the Maranhão Institute of Socioeconomic and Cartographic Studies (IMESC) and the Brazilian Service of Support for Micro and Small Enterprises (Sebrae). Featuring up methodologically as documentary research. From the information gathered were perceived the potential of extractive economy Craft of buriti fiber and its relevance to local development, the importance of the role of agencies in support of the entrepreneur and the protective measures of natural resources and the growing concern of social actors, both civil society, as government agents and artisanal production structure with the decrease in supply of raw materials and the impact to the environment.